Six-Hand Piano: Its Effectiveness as A Development for Piano Learning in Music Colleges - Samosir, Tanesya Hotris (Universitas Negeri Medan, 2024)
This research was conducted as an effort to address an issue regarding the decline in motivation for learning and practicing piano in intermediate-level piano classes at a music college. This has led to a stagnation in students' practical piano skills in specific piano techniques and theoretical abilities. The researcher proposes the development of learning through six-hand piano, with repertoire material created by the researcher entitled 'Explore'. This study applies the Robert K. Yin model of the case study method, conducted in three stages: Design, Execution, and Analysis. Sample selection utilized case-based sampling, involving three students from the class. Data collection included semi-structured interviews, observational analysis, document analysis, and literature review. To ensure the validity of the interview data, this study additionally employed Focus on Group Discussions (FGD). The analysis of the data encompassed within-case analysis, drawing conclusions, and comparison against theory. The findings in this research were identified as follows: Firstly, musical knowledge. Students gained a good understanding that enhanced their skills in several piano techniques, also music structure and form in repertoire. Secondly, several character values were identified based on the formulation of the 18 pillars of national character, which were observed throughout the learning process until its completion. These values were curiosity, responsibility, cooperation, discipline, hardwork, also friendly and communicative. These character values cultivate students' motivation to learn and practice the piano, thereby fostering musical knowledge